Cephalic marks and well‐being in newborns after operative vaginal delivery. Issue 2 (15th September 2021) - Gachon, Bertrand; Daressy, Elisa; Vanhecke, Johanne; Juinier Louarn, Christine; Papin, Sonia; Pierre, Fabrice; Fritel, Xavier
Abstract: Objectives: To compare the incidence of cephalic marks in newborns exposed to operative vaginal delivery and those who are not. We examined the factors associated with alterations in neonatal well‐being and with cephalic mark occurrence. Methods: Prospective study involving singleton term newborns delivered in a cephalic presentation. Newborns in the operative group were matched with newborns born on the same day without instruments required. A cephalic mark was defined as any mark or edema on the newborn's skin between 12 and 72 hours of life. Neonatal well‐being was assessed by analgesic consumption, neonatal discomfort (EDIN score of 1 or more), and prolonged hospitalization (4 days or more). We compared the operative and spontaneous groups and determined the relative risk (RR) for cephalic marks. We investigated the factors associated with alterations in neonatal well‐being and factors associated with cephalic mark occurrence in the case of operative delivery using multivariate logistic regression analysis. Results: A total of 135 newborns were included in each group. The incidence of cephalic marks was higher in the operative group (RR = 13.3 [6.0–29.5]). In case of operative delivery, cephalic marks were associated with neonatal discomfort (adjusted odds ratios [aOR] = 8.2 [2.2–30.6]) and analgesic consumption (aOR = 3.0 [1.2–7.1]). The number of cephalic marks was higher in cases with sequential use of vacuum and forceps (aOR = 3.5 [1.1–11.7]) and forceps only deliveries (aOR = 3.0 [1.1–8.1]) relative to vacuum only deliveries. Conclusions: Operative delivery increases the risk of neonatal cephalic marks, which can negatively affect neonatal well‐being.